Optical properties of diamond-like carbon films subjected to ultraviolet irradiation - Klyui, N.I.; Litovchenko, V.G.; Lukyanov, A.N.; Klyui, A.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
Influence of UV irradiation on optical properties of the nitrogen doped diamond-like carbon (DLC) films was studied. Transparency spectra of the initial, UV irradiated and concentrated UV irradiated films were measured. Dependences of the optical bandgap on the nitrogen content were obtained from these spectra. Raman measurements revealed a decrease in the graphitic cluster size by two times after UV irradiation. It was shown that concentrated UV irradiation leads to smaller changes in comparison with nonconcentrated UV. Physical mechanism of air oxygen embedding into the DLC structure under UV irradiation is proposed to explain the changes in the properties of the films.